2022
DOI: 10.3390/ijms23021003
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of an In Vitro Mesenteric Lymph Node Cell Suspension Model and Its Possible Association with In Vivo Functional Evaluation

Abstract: In a previous study, we uncovered three immune-responsive patterns of gut microbes using an in vitro mesenteric lymph node cell suspension model, abbreviated as the MLN model hereafter. We used Akkermansia muciniphila and Clostridium butyricum as the first group directly inducing an immune response, Bifidobacterium sp. and Bacteroides sp. as the second group evoking an immune response with the help of stimuli (anti-CD3 and anti-CD28 antibodies), and Lactobacillus sp. as the third group blunting the immune resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…19,20 Our previous study demonstrated that treatment with B. bifidum strains reversed inflammatory responses and reduced colitis symptoms in acute 2,4,6trinitrobenzene sulfonic acid (TNBS)-treated mice. 21 We also observed that this protective effect of B. bifidum against acute colitis was strain-specific and correlated well with the immunomodulatory properties of the strains in the mesenteric lymph node (MLN) co-culture model. Based on this information, combined with our data from the in vitro discovery platform, we selected three B. bifidum strains (FJSWX19M5, FXJWS17M4 and FHENJZ3M6) and further compared the differences between those B. bifidum strains in alleviating TNBS-induced chronic colitis in mice.…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…19,20 Our previous study demonstrated that treatment with B. bifidum strains reversed inflammatory responses and reduced colitis symptoms in acute 2,4,6trinitrobenzene sulfonic acid (TNBS)-treated mice. 21 We also observed that this protective effect of B. bifidum against acute colitis was strain-specific and correlated well with the immunomodulatory properties of the strains in the mesenteric lymph node (MLN) co-culture model. Based on this information, combined with our data from the in vitro discovery platform, we selected three B. bifidum strains (FJSWX19M5, FXJWS17M4 and FHENJZ3M6) and further compared the differences between those B. bifidum strains in alleviating TNBS-induced chronic colitis in mice.…”
Section: Introductionsupporting
confidence: 60%
“…Briefly, the MLN was freshly removed from male TNBS-treated BALB/c mice, mechanically disrupted, and cultured in RPMI 1640 medium containing 10% fetal bovine serum (FBS), 1 mM anti-CD3, and anti-CD28 (eBioscience). The cell suspensions (1 × 10 6 ) were co-cultured with viable or unviable bacterial suspension (optical density 600, 0.5) in a 96-well plate at a volume of 10 : 1 for 72 h. 21 IL-10, IL-17, and IL-22 were quantified using the corresponding mouse ELISA kits (R&D Systems) and replicated three times.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…69 The bioactive compounds originating from symbiotic microbiota are crucial in forming the intestinal immune system and controlling IL-10 release. 124 It is possible to stimulate the production of IL-10 in Foxp3+ cells. Treg cells are paramount in establishing immune tolerance towards antigens on mucosal surfaces, effectively avoiding inflammation in the gastrointestinal tract.…”
Section: Effects Of Probiotics On T Cells In Ucmentioning
confidence: 99%
“…The intervention provided relief from body weight loss, mitigated colonic shortening and damage, reduced gut inflammation indicators, and restored colonic metabolism equilibrium in mice afflicted with TNBS‐induced chronic colitis 69 . The bioactive compounds originating from symbiotic microbiota are crucial in forming the intestinal immune system and controlling IL‐10 release 124 …”
Section: Effects Of Probiotics On T Cells In Ucmentioning
confidence: 99%